Revisiting the critical role of metallic ash elements in the development of hard carbon for advancing sodium-ion battery applications - Chun Wu; Wenjie Huang; Yinghao Zhang; Qinghang Chen; Li Li; Yajun Zhang; Xingqiao Wu; Shu-Lei Chou (eScience)
Hard carbon (HC) anodes in sodium-ion batteries (SIBs) are prized for their high capacity, durability, cost-efficiency, environmental sustainability, and safety. The metallic ash elements in HCs inevitably affect the overall performance of SIBs, however, the unclear role of metallic ash elements during carbonization and the electrochemical sodium storage process presents challenges for advancing HC design concepts. In this review, the traditional role of metallic ash element realized in the past and the deep understanding by a new sight from the view of intrinsic types in precursor matrix are initially introduced. Subsequently, the effect of catalyzing graphitization degree, constructing pore structure, tuning SEI formation and tailoring defects of the HCs regulated by extrinsic factors introduced through experimental conditions in recent years are comprehensively summarized. Additionally, future development prospects and perspectives on the research about metallic ash element in HC are also briefly outlined. It is believed that this review can deliver noteworthy viewpoints by introducing metallic ash elements, for the continued development of adjusting the microstructure of HCs at the nanoscale to actualize high-performance SIBs.